Economy and punishment: current theories through a peripheral perspective - Stegemann Dieter, Mauricio (Southernising criminology, 2024)
The long-lasting controversy over the relationship between crime and the economy still animates several divergences that characterise some of the main criminological theories today. That is the case especially when it comes to explanations regarding the prison boom experienced by several countries during the 20th century. Since so much of what was hypothesised has been extrapolated for different contexts, this paper critically analyses some prominent theories through the lens of the so-called Global South, most notably confronting them with the reality of Brazil. Since some of the developments that apparently prompted such noticeable outcomes in the realm of punishment over the past decades seem especially acute in the periphery, an analytical confrontation contributes to better understand not only what transcends the context in which such ideas were formulated, and so its applicability to the South. But, in doing so, it helps to assess overall what is superfluous and what is not in such elaborations.